2011
DOI: 10.1007/s13157-011-0196-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Seasonal Variability in Surface Water Chemistry in the Okavango Delta, Botswana: A Multivariate Approach

Abstract: The annual flood pulse in the Okavango Delta (Botswana), has a major influence on water chemistry and habitat. We explore spatial and temporal patterns in a suite of chemical variables, analysed from 98 sample points, across four regions, taken at different stages of the flood cycle. The major pattern in water chemistry is characterised by an increasing gradient in ionic concentration from deepwater sites in the Panhandle to more shallow, distal regions to the south. Concentrations of cations, anions, dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 27 publications
8
41
1
Order By: Relevance
“…The order of solutes in concentration was Ca > Na > K > Mg, consistent with the findings of Sawula and Martins (1991) and Masamba and Muzila (2005). This was, however, contradictory to results of Mackay et al, (2011) who found a greater concentration of potassium than sodium. There has been little or no systematic change in water chemistry (major ions) over the years, with calcium the dominant cation in the Delta (Sawula and Martins, 1991;Mackay et al, 2011).…”
Section: System-scale Longitudinal Gradientcontrasting
confidence: 96%
See 3 more Smart Citations
“…The order of solutes in concentration was Ca > Na > K > Mg, consistent with the findings of Sawula and Martins (1991) and Masamba and Muzila (2005). This was, however, contradictory to results of Mackay et al, (2011) who found a greater concentration of potassium than sodium. There has been little or no systematic change in water chemistry (major ions) over the years, with calcium the dominant cation in the Delta (Sawula and Martins, 1991;Mackay et al, 2011).…”
Section: System-scale Longitudinal Gradientcontrasting
confidence: 96%
“…This implies that there must be some differentiation in the processes affecting individual ions. The concentrations of major cations (Ca, K, Mg and Na) increased generally throughout the Delta for surface waters, similar to the trends reported by Sawula and Martins (1991) and Mackay et al (2011). This correlates well with a general increase in conductivity along the Delta distributaries.…”
Section: System-scale Longitudinal Gradientsupporting
confidence: 84%
See 2 more Smart Citations
“…However, as hydro-period has been linked to changes in DOC concentration (Mackay et al 2011) and implicated as a potential driver of molecular diversity in wetlands (Hertkorn et al 2016), the predicted persistence of dry-down conditions may alter both DOC concentration and DOM composition. While % microbial is predicted to increase at TS under this scenario, DOC concentrations and the other three PARAFAC groups are predicted to decrease.…”
Section: Predicting Dom Response To Climate Changementioning
confidence: 99%